Uganda Economic Update, 13th Edition, May 2019 : Economic Development and Human Capital in Uganda - A Case for Investing More in Education - World Bank Group (World Bank, Washington, DC, 2019)
The World Bank’s analysis of cross-country data on human capital indicates that Uganda is underinvesting in the future productivity of its citizens. A child born in Uganda today will onlybe 38 percent as productive when she grows up as she could be if she enjoyed complete education and full health. Uganda is ranked among the countries in the lowest quartile of the Human Capital Index (HCI) distribution, with an index slightly lower than the average for the Sub-Saharan Africa (SSA) region, and below what would be predicted by its income level. Uganda’s low ranking in the HCI is mainly due to the country’s low education outcomes. A child born today in Uganda is expected to complete only 7 years of education by age 18, compared to a regional average of 8.1. Because of the low levels of learning achievement in Uganda, this is only equivalent to 4.5 years of learning, with 2.5 years considered as “lost” due to poor quality of education (as shown by thequality-adjusted years of schooling component of the HCI). Uganda’s score on this componentis the lowest amongst the comparator countries and below the SSA average.